Analysis of motion of solid hydrogen tracer particles in oscillating superfluid flows - Zemma, E.; Luzuriaga, J.; Babuin, S. (IOP Publishing, 2014)
Fil: Zemma, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina